Amanita pallidoverruca, a new species of Amanita section Validae from the Hengduan Mountains, southwestern China - Cui, Yang-Yang; Yang, Zhu L.; Cai, Qing (Phytotaxa, 2022)
Amanita pallidoverruca, a new species of A. sect. Validae, is described from the Hengduan Mountains, southwestern China. This species is associated with Picea trees and is characterized by a greyish brown pileus decorated with dirty white to greyish warts, non-striate and non-appendiculate pileal margin, subapical annulus with a greyish yellow to olivaceous edge, and amyloid, ellipsoid basidiospores measuring 8–10 × 6–7 μm. Phylogenetic analyses based on nrLSU, ITS, rpb2 and tef1-α indicated that it is closely related to A. excelsa. Illustrated morphological descriptions, and comparisons with closely related and similar species are provided.